Adsorption of phenol on activated carbon obtained from date palm branches - Sameh Ahmed; E. S. Gogina; N. A. Makisha (Vestnik MGSU)
Introduction. Phenols are one of the main organic components present in the effluents of many industrial enterprises. However, the discharge of wastewater containing phenol is a priority due to its high toxicity to humans and animals, even at low concentrations. Activated carbon (AC) adsorption, which is one of the advanced purification processes, is widely used to purify water pollutants and the production of activated carbon from several carbon by-products of agriculture was also reported. In this regard, the purpose of this research was to study the adsorption of phenol on activated carbon based on date palm branches (DPB-AC) as a low-cost adsorbent.Materials and methods. DPB was used as a raw material for the production of AC by chemical activation of H3PO4. Adsorption experiments were carried out in batches. The kinetics and isotherms of adsorption were also investigated.Results. DPB-AC was obtained by chemical activation of date palm branches using H3PO4 (600 ℃, 60 min), and the specimen was designated as (DPB-AC-H3PO4). The results showed an AC yield of 52.7 %. The maximum efficiency of phenol adsorption was achieved at pH 7. In addition, phenol adsorption was well described by the kinetics of the pseudo second order with K2 = 0.0503 g/(mg·min). The phenol adsorption isotherm model followed the Langmuir model, where R2 was 0.9215 and KL = 0.0161 l/mg at 180-equilibrium time. The maximum adsorption capacity of phenol was 77.52 mg/g (mg of phenol absorbed/g of DPB-AC-H3PO4), which is a high value compared to many other results presented in the literature.Conclusions. In general, the results indicate that AC obtained from date palm branches can be a promising material for wastewater treatment, as well as an effective means to solve environmental pollution problems.